Нууруудын хөндийн газрын тосны систем - Д., Буян-Аривжих (Geological Issues, 2022)
This article discusses the Mesozoic petroleum system of the Nuuruudiin Khundii between the Altai and Khangai Mountain ranges. From Sharga Gobi on the right side to Khongor plain on the left side, the Nuuruudiin Khundii is a narrow basin elongating along the latitude. The sedimentary rocks that filled it are divided into 3 mega-sequences: pre-rift, syn-rift, and post-rift. There are 14 subbasins developed in different tectonic regimes such as foreland, rift and pull apart within the Nuuruudiin Khundii. This region’s widespread Mesozoic sedimentary rocks contain good quality oil-generating source rocks. Medium to coarse-grained sandstones and landslide-related megabreccias accumulated in lake-delta and fan-delta environments are potential reservoir rocks. Relatively thick lacustrine mudstones of the Shinkhudag Formation provide a reliable seal rock. Because the Altai and Khangai ranges are still tectonically active, stratigraphic, structural and mixed traps are abundantly developed in the basin. Although no economically viable oil deposits have yet been identified within the Lakes Valley, there are signs of oil generation and migration within the basin.